Bloodstream Infections in Pediatric Cancer Patients with Febrile Neutropenia at a Tertiary Cancer Center in Northeast India - Talukdar, Amrita; Barman, Rashmisnata; Hazarika, Munlima; Das, Gaurav (Asian Pacific Journal of Cancer Care, 2023)
Objective: This study aimed to investigate the pattern of microbial flora, their susceptibility patterns, and clinical variables associated with bloodstream infections in febrile neutropenic patients with solid tumors and hematological malignancies in the pediatric age group in Northeast India. Materials and Methods: This retrospective, observational study was conducted at a single tertiary care cancer center in Northeast India between January 1, 2020, and December 31, 2021. The study population included all patients under 18 years of age who developed febrile neutropenia during cancer treatment. Results: A total of 378 blood culture samples were analyzed. Febrile neutropenia was found in 252 patients (66.7%). Of these, 45 blood cultures were positive (17.8%). Gram-negative and gram-positive organisms accounted for 62% and 38% of all positive cultures, respectively. Escherichia coli (39%) was the most common gram-negative isolate, followed by Klebsiella pneumoniae (32%), Pseudomonas aeruginosa (18%), and Acinetobacter baumannii (7%). Coagulase-negative Staphylococci (CoNS) was the most common gram-positive isolate (47%). Sensitivity to beta-lactam/beta-lactamase inhibitor (BL/BLI) antibiotics, such as cefaperazone/sulbactam, was observed in 60% of Pseudomonas isolates. Sensitivity to colistin was noted in 89% of Klebsiella and 82% of E. coli isolates. The incidence of methicillin-resistant Staphylococcus aureus (MRSA) was 50%. Conclusion: Understanding the microbiological profile and resistance patterns among pediatric cancer patients with febrile neutropenia is crucial for establishing effective antimicrobial policies.